Ethnopharmacological survey on medicinal plants used in herbal drinks among the traditional communities of Pakistan. (26th May 2016) - Ahmad, Mushtaq; Khan, Muhammad Pukhtoon Zada; Mukhtar, Anam; Zafar, Muhammad; Sultana, Shazia; Jahan, Sarwat
Abstract: Ethnopharmacological relevance: There is very limited information regarding medicinal plants used by traditional healers in Pakistan, for treating wide-ranging diseases. Current study provides significant ethnopharmacological information, both qualitative and quantitative on medical plants in Pakistan and the pharmacological importance of herbal drinks, especially in the discovery of new drugs. Materials and methods: The current ethnomedicinal field study was conducted from various traditional communities of Pakistan to document usage of medicinal plants as herbal drinks. Data was collected through field interviews from local people and using semi-structured questionnaires. Data was analyzed using quantitative indices such as UV (use value), RFC (Relative frequency of citation), and FL (Fidelity level). Results: The present study recorded 217 plant species belonging to 174 genera and 69 families used in herbal drinks preparations. Major herbal preparations include decoctions, infusions and juice. According to use reports, significant species were Aloe vera, Artemisia fragrans, Allium cepa, Senegalia catechu, Alternanthera sessilis, Malva ludwigii, Arnebia benthamii, Cichorium intybus, Coccinia grandis, Dalbergia sissoo . Major ailment treated with herbal drinks include heartburn, fever, diarrhea, hypertension, and others. Use value (UV) varies from 0.23 to 0.02, with Mentha arvensis (0.23) having the highest value of UV followed by Mentha longifolia (0.22), Plantago lanceolate (0.19), Achillea millefolium (0.18), Coriandrum sativum (0.18), Justicia adhatoda and Malva sylvestris (0.17). Values of RFC varies from 0.28 to 0.09 while Fidelity level (FL) among plants varies from 37.5 to 100. Alternanthera sessilis, Oxytropis lapponica, Millettia pinnata and Salvia bucharica had the highest FL value (100). Conclusion: The use of medicinal plants is prevalent in traditional communities of Pakistan. Different herbal preparations are in common practice including various herbal drinks a common tradition and much favoured herbal preparation in terms of its results and regarded as reciprocal to modern drugs. Therefore, suggesting further pharmacological, phytochemical evaluation for essential metabolites and chemical constituents. Graphical abstract: